Impact of diversity on organizational well-being: An exploratory study on the perception of the relationship between DEI and well-being in different business contexts - Romana, Fernando Acabado; Costa, Cláudia; Gestoso, Carlos Guillen; Lopes, Albino Anjos (Edelweiss Applied Science and Technology, 2026)
This study aims to conduct an exploratory analysis of the perception of the relationship between Diversity and Organizational Well-Being in companies at different levels of maturity in Diversity, Equity, and Inclusion (DEI). The literature suggests that companies with DEI practices may more easily achieve higher levels of Organizational Well-Being. It is also acknowledged in the literature that larger companies may more effectively implement inclusive practices within their teams, not only because they tend to have more diverse teams but also due to their greater potential for investment in this area. Given that the majority of the Portuguese business landscape is composed of small and medium-sized enterprises (SMEs), this study holds particular relevance within the national context. Therefore, this work seeks to embody an exploratory study, considering the limitations of time and sample size, which may provide insights into the subject matter to be further explored in a doctoral thesis, where generalizable results can be established.